Antibody cross-reactivity between casein and myelin-associated glycoprotein results in central nervous system demyelination - Chunder, Rittika; Weier, Alicia; Mäurer, Hannah; Luber, Nicolas; Enders, Michael; Luber, Gabriele; Heider, Thorsten; Spitzer, Alfred; Tacke, Sabine; Becker-Gotot, Janine; Kurts, Christian; Iyer, Radhika; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Multiple sclerosis (MS) is a neuroinflammatory demyelinating disease of the central nervous system (CNS) with a high socioeconomic relevance. The pathophysiology of MS, which is both complex and incompletely understood, is believed to be influenced by various environmental determinants, including diet. Since the 1990s, a correlation between the consumption of bovine milk products and MS prevalence has been debated. Here, we show that C57BL/6 mice immunized with bovine casein developed severe spinal cord pathology, in particular, demyelination, which was associated with the deposition of immunoglobulin G. Furthermore, we observed binding of serum from casein-immunized mice to mouse oligodendrocytes in CNS tissue sections and in culture where casein-specific antibodies induced complement-dependent pathology. We subsequently identified myelin-associated glycoprotein (MAG) as a cross-reactive antigenic target. The results obtained from the mouse model were complemented by clinical data showing that serum samples from patients with MS contained significantly higher B cell and antibody reactivity to bovine casein than those from patients with other neurologic diseases. This reactivity correlated with the B cell response to a mixture of CNS antigens and could again be attributed to MAG reactivity. While we acknowledge disease heterogeneity among individuals with MS, we believe that consumption of cow’s milk in a subset of patients with MS who have experienced a previous loss of tolerance to bovine casein may aggravate the disease. Our data suggest that patients with antibodies to bovine casein might benefit from restricting dairy products from their diet.
Gesehen am 09.04.2024